Analysis of Determinants of Capital Expenditure Allocation in West Sumatra Province - rahayu, resti (Jurnal Ilmu Ekonomi Terapan, 2019)
This study aims to analyze the effect of Regional Original Revenue, Balancing Funds, and financing surplus budget on Regency / City Capital Expenditures in West Sumatra Province in 2011 - 2017. Data used in this research is secondary data. To analyze the influence of PAD, Perimbanagan Funds, and SILPA on district/city Capital Expenditures in West Sumatra Province in 2011-2017, a panel data regression analysis method is used, which is a combination of inter-location data (cross section) and data from 19 districts / cities in Sumatra West and time series data with annual data from 2011-2017. The results of the study show that the right regression model used is the fixed effect model. With the results namely thevariable Original Regional Income has a positive effect on district / city capital expenditure in West Sumatra Province in 2011- 2017, while the Balancing Fund has a positive effect on district / city capital expenditure in West Sumatra Province in the year 2011 - 2017, and the financing surplus budget variable positive affects the Regency / City capital expenditure inWest Sumatra Province in 2011 - 2017.  Keywords: Regional Expenditures, Regional Original Revenue, Balancing Funds, Financing Surplus Budget. JEL: P48; R10